Quantum Ring Models and Action-Angle Variables; Journal of Computational and Theoretical Nanoscience; Vol. 40, iss. 22 - Bellucci S. Stefano; Nersessian A. P. Armen Petrosovich; Saghatelian A. Armen; Yeghikyan V. Vahagn (2011, 2011)
Title screen